(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Semenikhina O. V., Shamonya V. G., Udovichenko O. M., Yurchenko A. O. The problem of formation of abilities to interpret «computer» results in the process of Physics and Mathematics teachers training. The article describes the problem of formation of abilities to interpret adequate the results which are obtained by using IT resources. It is noted that possible ways of solving are: formation of theoretical knowledge and improvement skills to analyze the results critically, to analyze common mistakes, to give counterexamples, to use the test tasks and so on. The experience of realisation of such ways in the process of Physics and Mathematics teachers training was briefly described.